Characterıstıcs and survıval results of perıtoneal dıalysıs patıents sufferıng from covıd-19 ın turkey: a multıcenter natıonal study - AŞICIOĞLU, EBRU (My University, 2022)
AIMS: Although existing data suggest an increased mortality rate, data about the course of coronavirus disease 2019 (COVID-19) in peritoneal dialysis (PD) patients, its short-and long-term effects on the patient and technique survival are limited. Moreover, specific factors associated with increased risk of death have not been clearly defined yet. Therefore, we aimed to study the characteristics of PD patients with COVID-19, determine the short-term mortality and other medical complications, and delineate the factors associated with COVID-19 outcome. METHOD: This national multicenter study included all PD patients who had confirmed severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection based on positive reverse transcriptase-polymerase chain reaction testing of a nasopharyngeal swab recorded in this database from the attending 27 PD centers. The demographic data, comorbidities, medications used, PD-related data were recorded as well as clinical, laboratory and radiological findings of COVID-19 and outcomes at the end of the first month were recorded. RESULTS: We enrolled 142 COVID-19 patients (median age 52 years). A total of 58.2% of patients had mild disease at diagnosis, lung involvement was detected in 60.8% of patients. A total of 83 (58.4%) patients were hospitalized, 31 (21.8%) patients were admitted to intensive care unit and 24 needed mechanical ventilation. A total of 15 (10.5%) patients were switched to hemodialysis and hemodiafiltration was performed for 4 (2.8%) patients. Persisting pulmonary symptoms (n = 27), lower respiratory system infection (n = 12), rehospitalization for any reason (n = 24), malnutrition (n = 6), hypervolemia (n = 13), peritonitis (n = 7), ultrafiltration failure (n = 7) and in PD modality change (n = 8) were reported in survivors. During the 1 month from the diagnosis of COVID-19, 26 patients (18.31%) died. The non-survivor group was older and comorbidities were more prevalent. Fever, dyspnea, cough, serious-vital disease at presentation, bilateral pulmonary involvement and pleural effusion were more frequent among non-survivors. Age (OR1.102;95% CI 1.032- 1.117;P0.004), moderate-severe clinical disease at presentation (OR26.825;95% CI 4.578-157.172;P < 0.001) and CRP levels (OR1.008;95% CI;1.000-1.016;P0.040) were associated with increased first-month mortality in multivariate analysis. CONCLUSION: Early mortality rate and medical complications are quite high in PD patients with COVID-19. Age, clinical severity of COVID-19 and baseline CRP level are the independent parameters associated with mortality.
Keywords: Tıp; Dahili Tıp Bilimleri; İç Hastalıkları; Nefroloji; Sağlık Bilimleri; Medicine; Internal Medicine Sciences; Internal Diseases; Nephrology; Health Sciences; TRANSPLANTASYON; Klinik Tıp; Klinik Tıp (MED); ÜROLOJİ VE NEFROLOJİ; TRANSPLANTATION; CLINICAL MEDICINE; Clinical Medicine (MED); UROLOGY & NEPHROLOGY; Üroloji; Transplantasyon; Urology; Transplantation